Pengaruh Ineffective Monitoring, Sistem Pengendalian Internal, dan Budaya Organisasi Terhadap Kinerja Keuangan BUMDes Kecamatan Kubutambahan - Astari, Ketut Mei; Musmini, Lucy Sri (Jurnal Akuntansi Profesi, 2025)
This study aims to examine the influence of ineffective monitoring, internal control systems, and organization culture on the financial performance in BUMDes Kubutambahan Disrict. This study ia a quantitative approach with a multiple liniar regression analysis method.The population consists of all BUMDes in Kubutambahan Disctict. Through purposive sampling techniques, a sample of 11 BUMDes was obtained with a total of 77 respondents. Data were collectde using a questionnaire instument. Data analysis wasconducted using multiple linear regression with IBM SPSS version 27. The resultsof this study indicate that (1) ineffective monitoring has a negatif and significant effect on the financial performance of BUMDes in the Kubutambahan Disstrict; (2) internal control systems have a positive and significant effect on financial performance in the Kubutambahan District; and (3) organizational culture has a positive and significant effect on financial performance in the Kubutambahan District.